Stretchable fiber‐shaped aqueous aluminum ion batteries - Xiong, Ting; He, Bing; Zhou, Tianzhu; Wang, Zhe; Wang, Zhixun; Xin, Jiwu; Zhang, Haozhe; Zhou, Xuhui; Liu, Yanting; Wei, Lei (EcoMat (Beijing, China), 2022)
The emerging wearable electronics have significantly motivated the development of fiber‐shaped batteries with excellent electrochemical performance, safety, and flexibility. Aluminum (Al) ion batteries are potential candidates due to their high natural abundance, three‐electron‐redox behavior, and low cost. However, the integration of Al ion battery into wearable electronics remains unexplored. Herein, a stretchable fiber‐shaped aqueous Al ion battery is reported, which involves manganese hexacyanoferrate cathode, graphene oxide decorated MoO3 anode, and hydrogel electrolyte. The resulting fiber‐shaped battery exhibits good stretching properties and cycling stability (91.6% over 100 cycles at 1 A cm−3). Moreover, by employing a rocking‐chair energy storage mechanism, the fiber‐shaped battery offers a high specific capacity of 42 mAh cm−3 at 0.5 A cm−3, corresponding to a high specific energy of 30.6 mWh cm−3. As a demonstration, the fiber‐based Al ion batteries are integrated into wearable textiles to power LED light, demonstrating the feasibility in stretchable and wearable electronics. A stretchable fiber‐shaped aqueous Al ion battery is proposed by using manganese hexacyanoferrate cathode and graphene oxide decorated MoO3 anode separated by hydrogel electrolyte. The as‐prepared fiber‐shaped Al ion battery with a helical structure exhibits good stretching properties and cycling stability, showing promising prospects in stretchable flexible electronics and wearable energy textiles.